WHY DO STUDENTS WANT TO STUDY ABROAD? - Sattorova Khadicha Inayat qizi; Sattarov Inayat Saparbayevich (Scholars Digest Publishing, 2024)
Many students decide to study in another country - Korea, Great Britain, Germany, etc. The obvious reasons are the quality of education in foreign universities, work abroad, business contacts around the world. But there are other benefits as well. In this article, we will tell you why you should study abroad.